Analisis Sentimen Pada Postingan Akun @Hermanderu67 Dan Influencer Palembang Di Instagram Selama Pilgub 2024 Dalam Menggunakan Klasifikasi Naive Bayes - Alfansuriy Rahmanda Ikhsan; Norma Juainah; Najmi Muhammad Fadli (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This research aims to analyze public sentiment on Instagram posts from the @hermanderu67 account and several Palembang influencers during the 2024 South Sumatra gubernatorial election. Using the Naïve Bayes classification method, this study examines user comments to identify the tendencies of positive, negative, and neutral sentiments toward the political messages conveyed. The analysis is based on the growing phenomenon of social media as a political campaign arena, particularly among young voters, where public opinion is largely shaped through rapid and massive digital interactions.The findings indicate that Herman Deru’s political communication strategy through social media was relatively successful in building a positive image, as reflected by the dominance of positive sentiments in user comments. However, the presence of negative and neutral sentiments also reveals that social media is a dynamic space of political discourse, where criticism and appreciation coexist. This study affirms that social media functions not only as a channel for information distribution but also as a digital political arena that significantly influences public opinion and voter preferences.